Otimização de parâmetros de processamento de pinos por atrito em unidade com capacidade de 245kN - Caixeta, Lucas Antônio (2011)
Nowadays, one of the main problems faced by oil exploitation industries is the formation of cracks in offshore production units. In these classified areas, the Friction Hydro Pillar Processing has some advantages when compared to the arc-voltaic welding, which is widely used to perform these repairs. Some of them are the lower temperatures during the process and also the reduction of the surroundings influences in the quality of these repairs. This work presents the results concerning the optimization of some important parameters of the process performed by a Friction Pillar Processing unit able to apply axial loads up to 245 kN. This technique consists of filling a hole, through the use of a consumable rod under a controlled rotation speed and pressed against the hole. The friction between the surfaces increases their temperatures reducing the yield strength of the materials involved allowing a metallurgical bond between the parts. Among the process parameters to be optimized there are: axial load, rotation speed and burn length. For this, the PID control techniques were applied and a specific study of the controller boards was also accomplished. After this, some tests were performed to evaluate proposed solutions and also to identify the operational ranges of the equipment. The performed test matrices allowed the identification of these ranges and also validated the new optimal parameters proposed in this work. Moreover, the mechanical properties of each test were evaluated by means of hardness tests and microstructure analysis.